Smart microgrid with the internet of things for adequate energy management and analysis. (March 2023) - Sitharthan, R; Vimal, S; Verma, Amit; Karthikeyan, Madurakavi; Dhanabalan, Shanmuga Sundar; Prabaharan, Natarajan; Rajesh, M; Eswaran, T
Abstract: Smart microgrid sounds familiar in recent days for their advanced electrification in rural/urban areas without the support of a grid network. Energy management and control can provide stability to the microgrid when there is a sudden change in loads. In this paper, the Internet of Things (IoT) has been used with the microgrid for energy management and analysis. The obtained result identifies the performance and operation of the IoT-based energy management and analysis in the smart microgrid. The proposed system identifies the demand pattern and allows the microgrid to supply power accordingly. In case of uncertain demand, the proposed system initiates the user to isolate and protects the microgrid. The experimental setup has been developed with PV/Wind and Piezo based 2.5 kW hybrid power generation system and the obtained results have been compared with competitive technologies. The IoT assessment has been carried out using Thinkspeak and MATLAB tools.